1999
DOI: 10.1007/s004210050639
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations in ventilatory and cardiorespiratory responses to submaximal treadmill exercise in females

Abstract: Diurnal variations in ventilatory and cardiorespiratory responses to submaximal treadmill exercise were analysed in 11 eumenorrhoeic women and in 10 women using monophasic oral contraceptives. Subjects performed submaximal treadmill exercise at three intensities averaging 7, 8, and 9 km x h(-1), each for 4 min at 0800, 1300 and 1700 hours, assigned randomly on 3 separate days. Rectal temperature was measured before (T(rec(b))) and after (T(rec(a))) exercise. Cardiac frequency (f(c)), ventilation (V(E)), oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 18 publications
(25 reference statements)
0
25
0
Order By: Relevance
“…Hence, when using the D max method, it is difficult to determine which of these possibilities account for the change in the determination of Th lac . It might be that the reason why only HR and _ V _ O 2 follow a circadian rhythm when used to describe the ''threshold'' is because these two variables exhibit rhythmicity when exercise is submaximal (Reilly et al 1984;Giacomoni et al 1999), and it is not the blood lactate concentration per se that changes to any great extent. To determine whether the actual amount of blood lactate changes during exercise due to circadian effects, the results of using the Th lac-4 mM can be examined.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Hence, when using the D max method, it is difficult to determine which of these possibilities account for the change in the determination of Th lac . It might be that the reason why only HR and _ V _ O 2 follow a circadian rhythm when used to describe the ''threshold'' is because these two variables exhibit rhythmicity when exercise is submaximal (Reilly et al 1984;Giacomoni et al 1999), and it is not the blood lactate concentration per se that changes to any great extent. To determine whether the actual amount of blood lactate changes during exercise due to circadian effects, the results of using the Th lac-4 mM can be examined.…”
Section: Discussionmentioning
confidence: 96%
“…The most distinctive rhythm observed is that of core body temperature, with a peak occurring at $1800 hours and a trough at $0600 hours (Å kerstedt 1979). The circadian rhythm in temperature persists during submaximal exercise (Reilly and Brooks 1982), as does that of heart rate (HR; Reilly et al 1984), oxygen consumption ( _ V _ O 2 ; Reilly and Brooks 1982;Giacomoni et al 1999) and pulmonary ventilation ( _ V E ; Reilly and Brooks 1982). The lactate threshold (Th lac ), defined as the point at which blood lactate increases exponentially with exercise intensity (Yeh et al 1983), has not been investigated thoroughly with respect to circadian rhythms.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies addressed the effect of time of day on performance by comparing performance at different time points independently of the previous training time. Circadian rhythms may affect athletic performances by variations in thermoregulatory, cardiocirculatory, ventilatory, respiratory, and metabolic responses both at rest and during aerobic exercise (4,(25)(26)(27)(28). In the present study, we did not address the best time of day to achieve the highest performance.…”
Section: Discussionmentioning
confidence: 99%
“…(Cohen and Muehl 1977;Cohen 1980). Although Callard et al (2001) and Cohen and Muehl (1977) found some evidence of circadian rhythmicity in working HR, other studies (Cohen 1980;Giacomoni et al 1999;Vaughan and Reilly 1975) did not fully confirm this. Differences between the studies can probably be attributed to varying work intensities (Drust et al 2005).…”
Section: Discussionmentioning
confidence: 82%